Pengelolaan Kegiatan Kewirausahaan Dalam Pengembangan Kreativitas Peserta Didik Di Mts Negeri 2 Surakarta Pada Program Market Day - Indah Kurniawati; Sukari (4, 2024)
This study was motivated by the management of entrepreneurial activities in the development of creativity of students MTs Negeri 2 Surakarta through the market day program which is a program with a new term used to be in the lessons of local content and now created a new program called market day. This study aims to determine the management of entrepreneurial activities in the development of creativity of students at MTs N 2 Surakarta on market day program. Schools play an important role in shaping the creativity of learners, by having a Market Day program makes a concrete example of the school's efforts in applying the values of character education in a real context. Character education programs such as Market Day are not only about learning theory, but also about practical experience. By engaging in activities such as these, learners have the opportunity to develop character values such as hard work, creativity, responsibility, confidence, and so on in real-life situations. Through the character education program implemented in MTs Negeri 2 Surakarta, students are expected not only to develop academically but also as individuals who have creativity. This study is a qualitative research with a case study approach because in this study including the type of Field Research. Data collection techniques using interviews, and documentation. Therefore, in the analysis of research data will use four main steps in this study, namely: data collection, data reduction, data presentation, conclusion. the results of research and discussion on the management of entrepreneurial activities in the development of students ' creativity in MTs N 2 Surakarta can be concluded that: 1. The management of entrepreneurial activities in the development of students ' creativity through the “Market Day” program at MTs Negeri 2 Surakarta has been well managed starting from the planning stage, creativity development and marketing techniques. 2. The planning of entrepreneurial activities is well planned 3. Implementation of “Market Day